The Catholic Church’s Pastoral Communications and Their Implications for Church-State Relations in Post-Colonial Zambia (1964-2026) - Chanda Armstrong (Darul Yasin Al Sys, 2026)
The Roman Catholic Church (RCC) has historically played a significant role in shaping political, economic, and social discourse in Zambia, yet the evolution of its relationship with the State across successive political regimes requires further systematic examination. This study traces the historical trajectory of RCC–state relations in Zambia from independence in 1964 to 2026 through pastoral letters issued by the Catholic Bishops’ Conference of Zambia on matters of national concern. It aims to analyze the development and dynamics of RCC–state relations, examine the implications of pastoral communication for these relations, and propose a communication framework for reducing institutional tension. A qualitative research approach was employed, drawing on literature review, document analysis, and narrative analysis, with the data subsequently analyzed thematically. Guided by political-institutional transformation theory, the study examines changes in church–state relations across political transitions, particularly from the United National Independence Party (UNIP) era to the current United Party for National Development (UPND) administration. The findings reveal that pastoral statements on the state of the nation have a dual implication: they enable the RCC to advocate for social justice and freedoms and to provide institutional checks and balances, while simultaneously contributing to tensions and widening the relational gap between the Church and the State. The study concludes that pastoral communication remains an influential mechanism through which the RCC engages with governance and national development, but its effectiveness depends on communication structures capable of balancing prophetic advocacy with constructive institutional engagement. Accordingly, the study recommends the re-evaluation and adoption of communication structures that foster cooperation, sustained dialogue, and mutual understanding in the interests of the Zambian people and national development. This study contributes to the literature on church–state relations by providing a historically grounded analysis of pastoral communication in Zambia and by proposing a framework for strengthening sustainable dialogue between religious and state institutions.